Produk Ruang Tunggu Bandar Udara Berbasis Nilai Budaya - Preiscylia Jennifer Liemena; Mariana Wibowo; M. Taufan Rizqy (Intra, 2018)
The design of semi-private space in the airport waiting room, especially on the island of Java is based on various considerations. The lifestyle of users changes of modern society, who spend more time conducting activities in public area. Make private activities can not be fulfilled maximally, hence the design of semi-private space proposed can answer the existing demands. Also, due to the lack of application of natural wealth and culture owned by Indonesia in the existing design. The using of rattan material is one of Indonesia's high potential natural resources but has not been fully utilized. In addition to the airport has a large area that is still widely available, the airport becomes a relevant place for the design application because it is the main entrance gate and much traversed by people and tourists. The concepts raised for each region in this design take the idea of traditional cultural ideas, especially the local dance that comes from the location of the design reference. The concept is applied in the product of semi private space, work chair, table, lounge chair, stool, bench, lamp, and storefront board. The design results can provide different experiences, impacts, and meet the needs of airport users both in East Java, Central Java, and West Java.